As políticas de ações afirmativas no ensino superior sob a ótica dos gestores: o caso da Universidade Federal do Rio Grande do Sul - Gregório Durlo Grisa; Bernardo Mattes Caprara (Ciências Sociais Unisinos)
This article deals with the social representations of academic managers about the aims and symbolic impact of affirmative action policies in higher education, with reference to the experience of the Federal University of Rio Grande do Sul (UFRGS). These managers’ interpretations of affirmative action are understood using concepts such as new institu-tional framework and institutional racism, proposed by Santos and Silvério, respectively. The results show that there is a weak monitoring of the implementation of this public policy and that, with few exceptions, managers do not master the legal and historical details related to quotas and keep a certain distance from the political commitment to its success. There is a great variety of conceptions on matters linked to quotas, such as racism and the social role of the university. A dispute over political hegemony is observed in the management area and, at the same time, views of an elitist nature are identified. Finally, it is noteworthy that some strategic positions are occupied by people who see legitimacy in demands for the democratization of the university and for the recognition of certain social groups.